Wife, Inc. : The Business of Marriage in the Twenty-First Century - Leonard, Suzanne (Book collections on Project MUSE., 2018)
After a half century of battling for gender equality, women have been freed from the necessity of securing a husband for economic stability, sexual fulfillment, or procreation. Marriage is a choice, and increasingly women (and men) are opting out. Yet despite these changes, the cultural power of marriage has burgeoned. What was once an obligation has become an exclusive club into which heterosexual women with the right amount of self-discipline may win entry. The newly exalted professionalized wife is no longer reliant on her husband's status or money; instead she can wield her own power provided she can successfully manage the business of being a wife. Wife, Inc. tells a fiercely contemporary story revealing that today's wives do not labor in the home. Instead, the work of wifedom occurs in online dating sites, on reality television, in social media, and on the campaign trail. No longer the stuff of marriage vows, these realms are now controlled by brand management and marketability. To prosper, women must appear confident, empowered, and sexually savvy. Suzanne Leonard follows women as they date, prepare to wed, and toil as wives, using examples from popular culture in order to reveal marriage's newly professionalized role in the lives of American women. Being a wife is a business that takes a lot more than a vow to maintain.